Compatibility between Menstrual Pictogram Assessment and Haemoglobin Assessment in Abnormal Uterine Bleeding: Uji Kesesuian Pemeriksaan Piktogram Menstruasi dengan Pemeriksaan Hemoglobin pada Pasien Perdarahan Uterus Abnormal - Fitri Yulianti; Heriyadi Manan; Awan Nurtjahyo; Syarif Husin (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective: To determine the amount of wasted blood and diagnosedAUB and determine amount of decrease in haemoglobinlevels by adjusting the examination of menstrual pictogramwith haemoglobin.Methods: Diagnostic test was conducted in the DepartmentObstetrics and Gynecology Dr. Mohammad Hoesin/Faculty ofMedicine Universitas Sriwijaya Palembang, start from January 2015through January 2017. Sample was obtained from 39 patients withabnormal uterine bleeding who meet the inclusion and exclusioncriteria. Frequency and distribution of data are described in tablesand cross analyze (cut-off point) to find cut points differencemenstrual pictogram and a decrease in haemoglobin levels usingROC curve. Accuracy is measured by the value of Kappa. Dataanalysis using SPSS version 21.Results: From 39 samples that obtained, majority characteristicsage > 35 years (59%), ideal BMI (59%) and multiparous(48.7%). From statistical analysis, there was significanceassociation between haemoglobin measurement toolsand menstrual pictogram (p = 0.063). Both measuring deviceshave compatibility in predicting the type of AUB (p = 0.047),with the degree of conformity is weak (Kappa = 0.232).Conclusion: Accuracy of menstrual pictogram examination andhaemoglobin has a weak degree of conformity, so menstrualpictogram examination can’t be used to determine a decrease inhaemoglobin levels. Menstrual pictogram menstruation only usedas an evaluation of therapeutic response.[Indones J Obstet Gynecol 2018; 6-3: 172-178]Keywords: abnormal uterine bleeding, haemoglobin, menstrual pictogram